Dana Pihak Ketiga dalam Pertumbuhan Aset dan Efisiensi, serta Tantangan Pengaruh Pembiayaan UMKM dan Manajemen Risiko pada BPRS di Indonesia - Yudi Siyamto; Sumadi (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze the effect of Third-Party Funds (TPF) and Micro, Small, and Medium Enterprises (MSME) financing on asset performance, fund intermediation efficiency, and financing risk of Islamic Rural Banks (BPRS) across Indonesian provinces during the 2020–2024 period. The research utilizes secondary data from the Islamic Banking Statistics published by the Financial Services Authority (OJK). Panel data regression analysis was conducted using Stata through three main models examining the determinants of assets, Financing to Deposit Ratio (FDR), and Non-Performing Financing (NPF). The findings reveal that TPF serves as the primary driver of asset growth in BPRS, while MSME financing positively and significantly enhances fund intermediation efficiency as reflected in the FDR. Conversely, neither TPF nor MSME financing significantly affect the NPF, suggesting the need to strengthen risk management and internal governance beyond the expansion of financing volume. These findings reinforce and extend the Islamic financial intermediation theory and provide practical policy insights to strengthen the strategic role of BPRS in advancing inclusive and sustainable Islamic microfinance.